Leading for Innovation: How Inclusive Leadership, Proactive Personality, and Creative Self-Efficacy Interact in Hospitality Workers - Suyoto; Hermin Endratno; Hengky Widhiandono; Fatmah Bagis (Cita konsultindo, 2026)
The purpose of this study is to analyze an empirical research model that examines how proactive personality traits, inclusive leadership, and creative self-efficacy influence creative work behavior in the hospitality industry. There were 162 respondents from hospitality employees in Indonesia who provided complete and usable responses. Purposive sampling with non-probability techniques is the method used for sampling. Partial Least Squares (PLS) was then used to examine the collected data. The analysis findings indicate that inclusive leadership, proactive personality traits, and creative self-efficacy exhibit significant beneficial effects on creative work practices among hospitality employees. The findings of this study have significant implications for human resource management practices and strategies in the hospitality sector, particularly in the context of Indonesia's rapidly growing tourism industry. The positive influence of proactive personality traits, inclusive leadership, and creative self-efficacy on creative work behavior suggests that hotel organizations can enhance innovation and service quality by fostering these characteristics among employees. Managers should prioritize inclusive leadership practices that encourage open communication, employee participation, and recognition, as this creates a supportive environment where creativity can thrive.